2015
DOI: 10.1177/0363199015572753
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Cultural Differentials of Contraceptive Usage in West Bengal

Abstract: Contraception, the prevention of pregnancy through temporary or permanent means, can act as an effective instrument for achieving population stabilization in any region. This study deals with the socioeconomic and cultural differentials influencing contraceptive use among presently married women aged between 20 and 49 years currently in the state of West Bengal, India, as discerned from National Family Health Survey (NFHS)-3 (2005)(2006) data. To examine the above, simple percentage distribution, cross tabulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
2
7
0
1
Order By: Relevance
“…These results are mostly in line with recent studies on contraceptive preferences in India (e.g. McNay et al (2003), Husain et al (2013), Rai and Unisa (2013), , De , Ram et al (2014), Mishra et al (2014) and Haque and Patel (2015)). However, as already discussed in Sections 1 and 2, our model provides a more global and flexible overview which is motivated by current family planning policies in India and avoids focusing only on specific aspects of contraceptive preferences in India.…”
Section: Interpretation Of the Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results are mostly in line with recent studies on contraceptive preferences in India (e.g. McNay et al (2003), Husain et al (2013), Rai and Unisa (2013), , De , Ram et al (2014), Mishra et al (2014) and Haque and Patel (2015)). However, as already discussed in Sections 1 and 2, our model provides a more global and flexible overview which is motivated by current family planning policies in India and avoids focusing only on specific aspects of contraceptive preferences in India.…”
Section: Interpretation Of the Resultssupporting
confidence: 90%
“…(), Mishra et al . () and Haque and Patel ()). However, as already discussed in Sections 1 and 2, our model provides a more global and flexible overview which is motivated by current family planning policies in India and avoids focusing only on specific aspects of contraceptive preferences in India.…”
Section: Sociodemographic Determinants Underlying the Contraceptive Cmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, married women who either read the newspaper, listened to radio or watched television for at least once a week were more likely to utilize modern contraceptive methods than women with no media exposure. Previous studies in Senegal and West Bengal (36,37), showed similar ndings. Mass media is a key strategy for increasing demand for use in health services (38).…”
Section: Discussionsupporting
confidence: 81%
“…The difference in socioeconomic status among such caste-based groups can also influence their access to health care and nutrition, consequently resulting in differing fertility rates (Planning Commission, 2008, based on NFHS-3 data of 2005-06). Attitudes regarding contraceptive practices and better living standards (by accepting smaller family ideals) have been much influenced by mass media and greater degrees of social interaction (diffusion process) (Haque & Patel, 2015), as evident in Andhra Pradesh, which attained low fertility in the 1990s despite having higher mortality and lower literacy rates than the national average (James, 1999;Kulkarni, 2011;Brahmanandam & Arokiasamy, 2016), notwithstanding the expected 'threshold socioeconomic effects' (Jain, 1981), before this media influence could become operative. The above observations allowed the framing of some hypotheses, as follows: H1: While economic development would usually result in fertility decline, this would not be the case always as in some locales affluent parents would prefer to have more children, being better able to bear the costs of childbearing/childrearing (possibly assuming children to be a source of economic security).…”
Section: Introductionmentioning
confidence: 99%